Novel pyrrolobenzodiazepine and pyrroloquinazoline scaffolds synthesized by a simple and highly selective Ugi/cyclization sequence. Issue 36 (30th August 2017) - Pertejo, Pablo; Peña-Calleja, Pablo; Carreira-Barral, Israel; Quesada, Roberto; Alejandro Cordero, Nicolás; Javier Rodríguez, Francisco; García-Valverde, María
Abstract : A simple Ugi/cyclization sequence furnishing two novel pyrrolo-fused N-heterocycle families selectively by controlling the temperature is described. Abstract : Pyrrolo[2, 1- c ][1, 4]benzodiazepines (PBDs) and other benzo-fused N-heterocycles constitute privileged structures found in numerous bioactive compounds. Thus, developing simple and selective syntheses to furnish these derivatives from easily accessible starting materials is an important and challenging goal. In this work, novel pyrrolobenzodiazepine and pyrroloquinazoline derivatives have been synthesized following a common two step synthetic strategy. This strategy involves a one-pot Ugi/cyclization sequence followed by a reduction with spontaneous thermocontrolled cyclization. The control of the temperature in this second step allows fully selective access to either pyrrolo[2, 1- c ][1, 4]benzodiazepine-3-ones6 or pyrrolo[2, 1- b ]quinazolines7 . Density functional theory (DFT) calculations have been carried out to rationalize this reactivity, identifying the kinetic and thermodynamic reaction products and offering insights into the cyclization pathways. These synthetic methodologies show the versatility of the Ugi reaction as a tool in the synthesis of heterocyclic compounds with a pseudopeptidic skeleton.